WORKSHOP JUNIOR DATA SCIENTIST - Mega Bagus Herlambang; Ni Made Sudri; Linda Theresia; Gadih Ranti; Yasmin Mauliddina; Silvia Merdikawati; Aditya Maulana; Dedes Bangkit Munawar; Nafia Rahmah (Universitas Pahlawan Tuanku Tambusai, 2025)
The Junior Data Scientist Workshop, conducted on August 25, 2024, was designed to introduce participants to foundational concepts in Data Science and essential data analysis tools, with a focus on the Orange platform. Five students with a keen interest in data science attended the event. The workshop utilized a blend of theoretical instruction and practical application, guiding participants through key processes such as data cleaning, statistical analysis, and data visualization. Post-workshop evaluations indicate that 85% of participants demonstrated a marked improvement in their understanding of Data Science concepts and methods. Despite the participants’ successful application of analysis techniques, several challenges were noted in comprehending complex statistical principles, suggesting a potential benefit from supplementary instructional sessions. This workshop has contributed significantly to advancing participants’ data literacy and analytical competencies, equipping them with critical skills essential for data-driven decision-making